Schools as Safety Nets: Break-Downs and Recovery in Reporting of Violence against Children - Damian Clarke; Pilar Larroulet; Daniel Paila\~nir; Daniela Quintana (Institute of Labor Economics (IZA), 2023)
Schools are a key channel in formal reporting of violence against children, but this channel broke down with the onset of the COVID-19 pandemic. We study how widespread such reporting declines are, and to what extent they were recovered once re-openings begin. Examining the universe of all criminal reports of violence against children in Chile, we observe sharp declines in reporting of all types of violence (psychological, physical, and sexual), and that full recovery in reporting had not occurred, even nearly 2 years following initial school closures. Our estimates suggest that school closure and incomplete re-opening resulted in around 2,800 'missing' reports of intra-family violence against children, 2,000 missing reports of sexual assault, and 230 missing reports of rape against children, equivalent to between 10-25 weeks of reporting at baseline. In the post-school closure period, we find that greater school attendance encourages faster and more complete recovery in reporting of violence against children, pointing to important non-cognitive costs of both school closure, and school absence.
Keywords: D10; I28; I18; K42; 330; violence against children; reporting; school closure; school attendance; COVID-19